AFTER IWANTGREATCARE: SERVICE USER FEEDBACK AS A MEANS OF REFINING THE IWANTGREATCARE QUESTIONNAIRE. Issue 1 (1st March 2014) - Bowyer, A; Finlay, I; Byrne, A; McCarthy, J; Sampson, C; Snow, V; Nelson, A
Abstract : Introduction: In 2009 the Palliative Care Implementation Board developed a survey to evaluate palliative care service provision in Wales. Through the use of the iWantGreatCare platform patients and carers, from inpatient and community settings, are able to share their experiences of care through 10 likert scales and a free-text section. Subsequently, qualitative analysis of the comments of patients and carers has highlighted areas of care not fully assessed in the scored results. Accordingly, this project now aims to use the qualitative findings to refine and test the questionnaire to ascertain whether the new iteration accommodates service users' priorities and concerns, whilst being pertinent and understandable. Aim(s) and method(s): Ethical approvals were gained in August 2013. The refined questionnaire was developed through an expert consensus day and is now being tested using semi-structured, cognitive interviews with patients (n=10) and carers (n=10) using palliative care services at two hospices in South Wales. The research sites aim to give a multifaceted insight in to the efficacy of the new questionnaire by gathering information from inpatient and community participants. Transcripts from interviews are being analysed thematically. Results: It is expected that the interviews will highlight minor areas for change within the questionnaire, while also providing a broader insight into the experiences of patients using community and inpatient palliative care services. Conclusion(s): Study results will be presented to the Palliative Care Implementation Board for their consideration and potential adaptation of the existing questionnaire.